2021
DOI: 10.4995/wrs.2021.13266
|View full text |Cite
|
Sign up to set email alerts
|

Health, performance and soiling of breeding does and their kits kept in two different housing systems on a German rabbit farm

Abstract: <p>The aim of the present study was to compare a new housing (NC) for rabbit does and their kits that complies with German welfare regulations with established wire mesh cages (CC) on a commercial rabbit farm. Rabbit does were single-housed from five days antepartum until weaning at 31 d postpartum either in large pens (80×80 cm with an open top) with slatted plastic flooring (11 mm slats and 11 mm gaps), nestbox, elevated platform (15% perforated) and different manipulable materials (NC) or in cages (70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…Indeed, we did not detect any difference in the occurrence of health concerns both for does and litters among the farms with different housing systems. Moreover, a previous study found a higher occurrence of mastitis and diarrhea in larger cages, which was due to the higher soiling of the floor because of an unsuitable footrest mat ( 36 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Indeed, we did not detect any difference in the occurrence of health concerns both for does and litters among the farms with different housing systems. Moreover, a previous study found a higher occurrence of mastitis and diarrhea in larger cages, which was due to the higher soiling of the floor because of an unsuitable footrest mat ( 36 ).…”
Section: Discussionmentioning
confidence: 97%
“…However, again according to EFSA ( 11 ), knowledge is missing about the space requirement to acceptably meet the behavioral and physiological needs of rabbits under farming conditions. Moreover, more space and locomotion possibilities can affect doe performance on-farm ( 12 , 35 ): some authors ( 36 ) observed higher body weight and weight gain in does housed in conventional cages than those kept in larger cages, while others reported few differences ( 35 ). In the case of reproducing does, an impairment in performance is especially expected when comparing conventional individual housing with collective housing systems, which has been related to aggression and stressful interactions among does rather than to space availability itself ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…et al (2019) оцінюють розвиток пододерматиту за шкалою від 0 до 3: 0 -шкіра і хутро неушкоджені, 1 -утворення алопеції, 2 -гіперкератоз (утворення характерних мозолів), 3 -поява ерозії, виразки на поверхні шкіри [8]. Також, для кролів запропоновано класифікацію, адаптовану під класифікацію пододерматитів птиці (Jekl V., 2012): 1 стадія -відсутність волосяного покриву; 2 стадія -еритема, місцевий набряк за збереженої цілісності шкіри на плантарній та/або пальмарній поверхні кінцівок; 3 стадія -ерозії або виразки, кровотечі, струп; 4 стадія -глибоке запалення із залученням сухожилок (тендовагініт); 5 стадія -остеомієліт, гнійний артрит [9]. Mancinelli Е.…”
Section: аналіз актуальних дослідженьunclassified